Analysis of Bank Collapse at “Tianzi-1” Revetment Section in Hunan Segment of Lower Jingjiang River in 2023 - CHEN Yi-min, LIN Dang, YANG Tian-tian, ZHENG Bao, ZHANG Guo-hua, LI Ling-yun, GUO Chao (长江科学院院报)
[Objectives] Since the operation of the Three Gorges Project and the cascade reservoirs in the upper reaches of the Yangtze River, the new water and sediment regime has caused large-scale and high-intensity continuous erosion in the Jingjiang River section of the middle Yangtze River, resulting in recurrent bank collapse incidents at some revetment sections. To investigate the causes of recent bank collapses at revetment sections and better respond to such dangerous situations, this study examines the sudden bank collapse and its emergency treatment at the “Tianzi-1” revetment section in the lower Jingjiang River in 2023. [Methods] Measured water and sediment data at Jianli station since 1990, annual erosion and deposition data of the lower Jingjiang River since 2003, and measured data on channel topographic changes and geological drilling before and after the bank collapse at the “Tianzi-1” section were used to analyze the causes. [Results] In November 2023, continuous cave-in-type bank collapses occurred at the “Tianzi-1” revetment section in the Hunan segment of the lower Jingjiang River, with collapse lengths of approximately 100 m and 35 m, respectively. The results showed that the bank collapse primarily resulted from continuous riverbed erosion under the clear-water discharge condition, significant changes in local river regime causing deep channel and thalweg migration toward banks, poor geological conditions of the riverbank slope, and the influence of prolonged low-to-medium water levels. Based on the characteristics of the dangerous situation, an underwater stone dumping method was adopted for emergency treatment of the collapsed section and the affected upper and lower reaches. [Conclusions] This recurrent bank collapse at the revetment section highlights that the lower Jingjiang River will continue to face severe threats of bank collapse for the foreseeable future. Without timely reinforcement measures, large-scale damage can occur to existing bank protection structures, seriously threatening flood control safety. Therefore, this study proposes medium-to-long-term governance measures, including establishing institutional frameworks as soon as possible, securing construction funding, strengthening dynamic monitoring of slope toe variations at dangerous sections, enhancing the development of bank failure control technologies, and improving the monitoring, early warning, and emergency response mechanisms for bank collapse.